LEADERSHIP EEFECTIVENESS AND SOCIAL REFORMS IN RISALE-I NUR - Said, Mohamed Mohamed Tolba; Umachandran, Krishnan (2018)
This paper aims to cover the philosophy of science or the religious Islamic epistemology through Bediuzzaman Said Nursi’s thought carried out with the fraternization of natural sciences with the religious sciences, to strengthen the truths arranged on modern advanced scientific beliefs and spiritual alignments for development, for guiding and enlightening the modern-day youth. The cautious use of freedom and its protection with clear definition on the liberty limits was narrated by Bediüzzaman Said Nursi’s Risale-i Nur (1910-1950), provided the desired the celestial and modern facts to right channelize with the determination to validate the evidences for Islam’s assurance for religious revival. Reasoning the ignorance in individuals and exploitation of supremacy for rigid unsophisticated ideals of moral values, Bediüzzaman Said Nursi’s prospered on the issue of the Islamic world from the oubliettes of inexperience and deficiency; with the spirit and liberal thought, that a superior demand on learning can place the society obsessed for development by protection from the onslaught which could disturb relationships for personal advantage, exclusive treatment and disenchanted extravaganza. Appeals to normalize the leadership character for materialism and the interest in properties have historically been connected to evolution, methodical substantiation of knowledge, and excellent protection for socio-economic expansion. To overcome numerous hindrances and sustained teaching with understandings of Islam, education needed to inspire erudition method towards development across all societies. Bediüzzaman Said Nursi’s solid propagandizing’s laid the foundation to peace and harmony do not use any force and avoid any disruption turned out to be effective, when it shared character and spiritual instruction. Core temperament and consciousness in its truthful real form will exhibit the quality of humankind, therefore and reveal facts about themselves.